Coastal Fishes of São Tomé and Príncipe islands, Gulf of Guinea (Eastern Atlantic Ocean)—an update - Wirtz, Peter; Ferreira, Carlos Eduardo L.; Floeter, Sergio R.; Fricke, Ronald; Gasparini, João Luiz; Iwamoto, Tomio; Rocha, Luiz; Sampaio, Cláudio L.s.; Schliewen, Ulrich K. (Zootaxa, 2007)
Here we report 59 new records of shore fishes for São Tomé and Príncipe islands (Gulf of Guinea), Eastern Atlantic Ocean. Ten of these are new species still to be described, including a new genus of a gobiid fish that lives in association with an axiid shrimp. A large proportion of the shore fishes of São Tomé and Principe occur on both sides of the Atlantic and many have their sister-species in the western Atlantic. To a lesser degree, there are also affinities to the western Indian Ocean.